PELAKSANAAN PENSERTIFIKATAN TANAH HAK MILIK SETELAH BERLAKUNYA PP NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (Studi Kasus di Kabupaten Cilacap) - , Cecilya Lukito; , Pudjiastuti, S.H.,SU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was intended to study implementation of land ownership certification in Cilacap and to identifiy factors causing people not registering their land. This type of research used in this study is that a juridical sociological study of law as a legal notice symptoms or social institutions. In juridical sociological research, the data examined are secondary data, to then proceed with the study of primary data in the field or to society. Respondent determined by purposive sampling technique that is non-random sampling technique. Informants in this study are official Deed of land in the district of Cilacap by one person, the Head of Administration Sub Cilacap district and village secretary. How research includes literature research and field research, using interview techniques. To analyze the data to use deductive method 1 Jl. Flores No. 09 Cilacap, Central Java 2 Lecture of Facultyof Law, Gadjahmada University, Yogyakarta . Result of the research indicated that implementation of land certification in Cilacap has run well but it did not run evenly due to insufficient fund from state budget or local budget. In determining location, BPN had difficulty of looking for information about owner of land without ownership certificate and there was less people awareness about the metter. Factors causing people not register their land is cost, status of hereditary land with parent still live and people education in which they have junior school.